Studies on the Utilization of Spent Heartwood of Acacia catechu (Khair) - Karnik, M. G.; Bhatia, Kuldip; Dev, Inder; Lal, Jai (Indian Forester, 1973)
These studies were made to explore the possible commercial utilization of the exhausted heartwood of Acacia catechu. The exhausted heartwood (residue left after extraction of katha aud cutch) is a waste material of the katha industry. The exhausted heartwood was analysed for its major chemical constituents and the optimum conditions to isolate cellulose suitable for cellulose based industries, from exhausted heartwood alone and from the mixture of exhausted heart and sap wood, have been described. Experiments were also undertaken to prepare cellulose gum and the data on its evaluation is incorporated in the article.